Acute effect of TBTCL on protein alteration in freshwater bivalve, Lamellidens marginalis - Ubarhande2, J.T. Jagtap1*, K.B. Shejule1; S.B. (International Multidisciplinary Research Journal, 2011)
The freshwater bivalves L. marginalis exposed to 3.5 ppm, 2.5 ppm, 1.8 ppm and 1.0 ppm concentration of tributyltin chloride on protein content in the tissue of gonad, gill and digestive glands up to 96 hours exposure respectively. Compare to control group there was significant change in protein contents from gonad, gill and digestive glands in tributyltin chloride exposed groups. The result showed that TBTCl induces significant depletion in protein metabolic profiles in gonad, gill and digestive glands might be due to increased proteolysis and possible utilization of the products of their degradation for metabolic purpose.